Study on soil stabilisation technique using lime & fly ash - Amiralian, Saeid (Curtin University, 2013)
A series of microanalytical (Optical microscopy, scanning electron microscopy, energy dispersive X-ray spectroscopy, X-ray diffraction, and Fourier transform infrared spectroscopy ) and geotechnical (standard compaction , hydraulic conductivity, one-dimensional consolidation, and direct shear) tests used for analysing the effectiveness of lime and fly ash on soil stabilisation from a chemical/elemental and geotechnical viewpoints. The geo-chemical analysis was revealed the creation of chemical components required for the chemical reaction, thereby improving the soil’s geotechnical performance.